NeuroViOme: a viral orfeome collection for studies of neurodegenerative disease - Benjamin Weller; Chung-Wen Lin; Simin Rothballer; Michael A. Calderwood; Pascal Falter-Braun; Claudia Falter (Journal of NeuroVirology, 2026)
Neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS) pose a global health challenge due to their progressive course and lack of curative therapies. These conditions lead to severe neurological decline, significantly impacting patient independence and quality of life, and ultimately result in lethal outcome. Emerging evidence suggests that viral infections contribute to the onset and progression of these neurological diseases, Leblanc and Vorberg (PLoS Pathog 18:e1010670, 2022), either by directly inducing neurological symptoms or by triggering immune responses resulting in neuropathology. Nevertheless, systematic studies of the direct interplay between viral and host proteins in neurodegeneration remain scarce. A key aspect of viral pathogenesis is direct interaction between viral and host proteins (protein–protein interactions, PPIs), which are essential for viral replication and can disrupt or redirect host cell function Kim et al. (Nat Biotechnol, 2022); Zhou et al. (Res Sq, 2022), potentially contributing to the development of diseases traditionally considered non-communicable. Understanding these molecular mechanisms is crucial for advancing diagnostic and therapeutic strategies in neurodegenerative conditions, particularly ALS and MS. To enable systematic studies of these interactions, we introduce NeuroViOme as ORFeome resource encompassing nearly all protein-coding sequences from nine viruses selected based on their prevalence, neurotropism, and mechanistic or epidemiological links to neurodegenerative processes. NeuroViOme includes ORFs from Enteroviruses (EV-A71, EV-D68, CVB3, Echovirus E30), Herpesviruses (HSV-1, EBV, HHV3/Varicella Zoster), the endogenous retrovirus HERV-K, and Polyomavirus JCPyV. To our knowledge, this represents the most comprehensive viral ORF set assembled for neurodegeneration research to date. The collection builds the foundation for interactome mapping and functional genomics analyses and provides a valuable basis for systematic studies of viral perturbations of host pathways.